Reflection of Kazakh-Russian bilingualism in children's language in education (based on a sociolinguistic survey) (Eurasian Journal of Philology Science and Education, 2023)
Bilingualism is one of the phenomena that is widespread in the world. The article determines the assimilation of Kazakh-Russian bilingualism in children's speech. In order to determine the level of mastering bilingualism, a sociolinguistic survey of 2nd grade Kazakh and Russian language students was conducted. All in all 31 pupils took part in the survey. There were 11 questions in the questionnaire. They were asked to determine the level of cognitive thinking and learning the grammar of the Kazakh language by children.The article also reviews the history and reasons for the formation of Kazakh-Russian bilingualism. The types of bilingualism in general linguistics and consequences of mastering two or more languages at an early age were shown.Questions such as «How often do your parents talk to you at home in Russian\ Kazakh?», «How well do you understand TV programs or movies in Russian\ Kazakh?», «Is reading in Kazakh\ Russian more difficult than in Russian\ Kazakh?», «I think it is important to understand and speak Russian / Kazakh», «Who do we call 'karyndas'?», «Find the Kazakh national game», «What is a baby sheep called?» were asked. According to the results of the survey, it was found that the consequences of Kazakh-Russian bilingualism in children's speech in the country affect the cognition of the Kazakh-speaking child, the misuse of language units in the Kazakh language.  It was also shown that full-fledged research is needed to determine the impact of Russian grammar in children's speech and the level of acquisition of Kazakh grammar by students mastering Kazakh as a second language. The article concluded with the opinion that at an early age a child should be taught only in their native language or only one language.Keywords: bilingualism, bilingualism in children's language, sociolinguistics, cognitive linguistics, Kazakh-Russian bilingualism